The isolation culture and screening of estuarin fungi by semi-solid fermentation of some agricultural wastes for feed supplements - Gacutan, Ma. Vicente
Cellulolytic fungi were baited on rice straw and bagasse in the estuarine waters of Batan, Aklan Province. among the forty-two species colleted, 21% were obligate marine fungi while the rest were either facultative marine organisms or transient terrestrial forms that survived the marine environment. The isolates that grew favorably on glucose-yeast extract-sea water agar (GYESWA) were subjected to the culture plate screening process for the selection of strains with high biomass index (BI) and fermentative potential or utility index (UI).